DETERMINANT FACTORS OF RUPIAH’S FLUCTUATION: the Flexible-Price Monetary APPROACH THROUGH JOHANSEN COINTEGRATION AND ERROR CORECTION MODEL - Noor Iskandarsyah (Pusbindiklat - LIPI, 2013)
n the free floating exchange rate system, fluctuation of exchange rate is determined by supply and demand factors. The monetary approach is a approach in the monetary teory to analyze of exchange rate fluctuation. In this approach, the fundamental factor or macro economic indicators are main factor to determine exchange rate fluctuation. The study aims to get the information about factors which influenced the exchange rate’s fluctuation, by using the Flexible-Price Monetary Approach in period of the free floating exchange rate system in Indonesia. By knowing the effect of each variable not only comes from domestic (Indonesia) but also international (the United States), this study analyzes which variables that have dominant factor to rupiah exchange rate toward US dollar especially in year 2000-2010. This study shows, both in the long and short term, all variables in the monetary model have significant impact to rupiah’s fluctuation. Variabel that have dominant factor in the long term is Indonesia GDP, but in the short term is America GDP.